Application of Azide-Alkyne Cycloaddition “Click Chemistry” for the Synthesis of Grb2 SH2 Domain-Binding Macrocycles - Choi, Won Jun (2006)
Copper (I) promoted [3+2] Huisgen cycloaddition of azides with terminal alkynes was used to prepare triazole-containing macrocycles based on the Grb2 SH2 domain-binding motif, “Pmp-Ac(6) c-Asn”, where Pmp and Ac(6) c stand for 4-phosphonomethylphenylalanine and 1-aminocyclohexanecarboxylic acid, respectively. When cycloaddition reactions were conducted at 1 mM substrate concentrations cyclization of monomeric units occurred. At 2 mM substrate concentrations the predominant products were macrocyclic dimers. In Grb2 SH2 domain-binding assays the monomeric (S)-Pmp-containing macrocycle exhibited a K(d) value of 0.23 μM, while the corresponding dimeric macrocycle was found to have greater than 50-fold higher affinity. The open-chain dimer was also found to have affinity equal to the dimeric macrocycle. This work represents the first application of “click chemistry” to the synthesis of SH2 domain-binding inhibitors and indicates its potential utility.